(untitled) - Monk, Ellen F. (Australia, 2010)
The book is organized into seven parts: database cases using Access, decision support cases using the Excel Scenario Manager, decision support cases using the Excel Solver, decision support cases using Basic Excel Functionality, integration cases using Access an Excel, advanced Excel skills using Excel.
Keywords: Microsoft Access,Microsoft Excel (Computer file),Business; Computer programs